2017
DOI: 10.1111/1462-2920.13841
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pseudomonas species secrete exolysin‐like toxins and provoke Caspase‐1‐dependent macrophage death

Abstract: Pathogenic bacteria secrete protein toxins that provoke apoptosis or necrosis of eukaryotic cells. Here, we developed a live-imaging method, based on incorporation of a DNA-intercalating dye into membrane-damaged host cells, to study the kinetics of primary bone marrow-derived macrophages (BMDMs) mortality induced by opportunistic pathogen Pseudomonas aeruginosa expressing either Type III Secretion System (T3SS) toxins or the pore-forming toxin, Exolysin (ExlA). We found that ExlA promotes the activation of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 92 publications
(172 reference statements)
3
32
0
Order By: Relevance
“…When indicated triton X100 (Sigma) at 1% (v/v) was added at the end of the kinetics to further control cell death/viability. Area under the curve were computed using Prism software (GraphPad) to obtain a single quantitative readout of the full kinetics as recently described [ 64 ]. Gliotoxin (Enzo Pharma) and Nigericin (Sigma) were used at 5 μM, the latter after a 3 h priming with LPS at 100 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…When indicated triton X100 (Sigma) at 1% (v/v) was added at the end of the kinetics to further control cell death/viability. Area under the curve were computed using Prism software (GraphPad) to obtain a single quantitative readout of the full kinetics as recently described [ 64 ]. Gliotoxin (Enzo Pharma) and Nigericin (Sigma) were used at 5 μM, the latter after a 3 h priming with LPS at 100 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Active caspase-1 induces the maturation of the pro-IL-1β into IL-1β. Caspase-1 also provokes the rupture of macrophage plasma membrane by a process called pyroptosis, releasing massive quantities of pro-inflammatory IL-1β in the surrounding environment [ 20 ] ( Figure 2 B). Therefore, similarly to T3SS-positive strains, ExlA-secreting bacteria are capable of triggering inflammasome activation and pro-inflammatory cell death of macrophages in vitro.…”
Section: Caspase-1 Dependent Death Of Macrophagesmentioning
confidence: 99%
“…This genetic organization is conserved in all clonal outliers sequenced to date. Bioinformatics analysis performed on all genomes available in the Pseudomonas database [ 10 ] revealed the presence of exlBA genes in several Pseudomonas species, including P. putida , P. entomophila , P. protegens and P. fluorescens [ 20 ]. Here we bring insights regarding the structural and functional features of this novel toxin acquired by some multi-resistant P. aeruginosa strains.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we found that other Pseudomonas species, such as Pseudomonas putida, Pseudomonas protegens and Pseudomonas entomophila, express ExlA-like toxins which are responsible for pyroptotic death of macrophages (52). Orthologs of vfr and cyaB genes are present in these species, inferring a common regulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%